The effect of oligo(trimethylene carbonate) addition on the stiffness of acrylic bone cement. Issue 1 (1st January 2016) - Persson, Cecilia; López, Alejandro; Fathali, Hoda; Hoess, Andreas; Rojas, Ramiro; Karlsson Ott, Marjam; Hilborn, Jöns; Engqvist, Håkan
ABSTRACT: With the increasing elderly population an increase in the number of bony fractures associated to age-related diseases such as osteoporosis also follows. The relatively high stiffness of the acrylic bone cements used in these patients has been suggested to give raise to a suboptimal load distribution surrounding the cement in vivo, and hence contribute to clinical complications, such as additional fractures. The aim of this study was to develop a low-modulus bone cement, based on currently used, commercially available poly(methyl methacrylate) (PMMA) cements for vertebroplasty. To this end, acrylate end-functionalized oligo(trimethylene carbonate) (oTMC) was incorporated into the cements, and the resulting compressive mechanical properties were evaluated, as well as the cytotoxic and handling properties of selected formulations. Sixteen wt%oTMC was needed in the vertebroplastic cement Osteopal V to achieve an elastic modulus of 1063 MPa (SD 74), which gave a corresponding compressive strength of 46.1 MPa (SD 1.9). Cement extracts taken at 1 and 12 hours gave a reduced MG-63 cell viability in most cases, while extracts taken at 24 hours had no significant effect on cell behavior. The modification also gave an increase in setting time, from 14.7 min (SD 1.7) to 18.0 min (SD 0.9), and a decrease in maximum polymerization temperature, from 41.5°C (SD 3.4) to 30.7°C (SD 1.4). While further evaluation of other relevant properties, such as injectability and in vivo biocompatibility, remains to be done, the results presented herein are promising in terms of approaching clinically applicable bone cements with a lower stiffness.